Feature-rich electronic properties of aluminum-adsorbed graphenes. (August 2017) - Lin, Shih-Yang; Lin, Yu-Tsung; Tran, Ngoc Thanh Thuy; Su, Wu-Pei; Lin, Ming-Fa
Abstract: The electronic properties of aluminum-adsorbed graphenes enriched by multi-orbital hybridizations are investigated by using first-principles calculations. The enriched features include the quasi-rigid red shifts of the carbon-related energy bands, the Al-dominated valence and conduction bands, and enhanced density of states (DOS) near the Dirac cone. The Al- and alkali-induced high free carrier densities are almost the same. There exist certain important differences among the Al-, alkali- and halogen-adsorbed graphenes, such as, the buckled or planar graphene, the preserved or seriously distorted Dirac cone, the presence or absence of the adatom-dominated valence bands, the free electrons or holes, the degenerate or split spin-related states, and the split peaks in DOS. The similarities and differences come mainly from the diverse orbital hybridizations in adatom-C bonds, reflected in the atom-dominated bands, the spatial charge distributions and the orbital-projected DOS. Graphical abstract: